1994
DOI: 10.1111/j.1472-765x.1994.tb00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aeromonas hydrophila hybridization groups and their virulence properties in Australasian clinical and environmental strains

Abstract: A total of 182 Aeromonas hydrophila strains isolated from environmental (food and water) and clinical (stool and other sources) samples taken in mainland Australia, Tasmania and New Zealand were assigned to one of three DNA/DNA hybridization groups (HGs) on the basis of biochemical characteristics, and tested with regard to their ability to produce virulence factors. Strains from HG2 were rarely isolated; strains from HG1 were most commonly isolated from clinical sources; and strains from HG3 formed the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Kirov, Hudson, Hayward, and Mott (1994) assigned 182 A. hydrophila strains isolated from the environmental (food and water), clinical (stool) and other sources to one of three HGs on the basis of biochemical characteristics, and tested them with regard to their ability to produce virulence factors. Strains HG1 (nine, common isolates from clinical sources) were more likely to produce virulence factors, while HG3 strains formed the majority of environmental isolates.…”
Section: Characteristics Of a Hydrophilamentioning
confidence: 99%
“…Kirov, Hudson, Hayward, and Mott (1994) assigned 182 A. hydrophila strains isolated from the environmental (food and water), clinical (stool) and other sources to one of three HGs on the basis of biochemical characteristics, and tested them with regard to their ability to produce virulence factors. Strains HG1 (nine, common isolates from clinical sources) were more likely to produce virulence factors, while HG3 strains formed the majority of environmental isolates.…”
Section: Characteristics Of a Hydrophilamentioning
confidence: 99%
“…Enterotoxic activity in two of three mice is considered as indicative of virulence potential (Kirov et al . 1994).…”
Section: Enterotoxic Activitymentioning
confidence: 99%
“…However, some studies showed only certain species have displayed clinical importance for aquatic animals and are recognized as potential pathogens causing diseases (10). In recent years, some new aquatic pathogens belong to the genus Aeromonas have been reported (18,24).…”
Section: Introductionmentioning
confidence: 99%